Law Enforcement Against Human Trafficking: Challenges And Solutions From A Criminal Law Perspective - Ika Andri Mellana; Fristia Berdian Tamza; Ahmad Irzal Fardiansyah (International Journal Labs, 2025)
Human trafficking is a complex transnational crime with widespread impacts on human dignity and worth. In Indonesia, efforts to eradicate TIP are regulated by Law Number 21 of 2007 concerning the Eradication of the Crime of TIP, which serves as the lex specialis for handling this case. However, reality shows that law enforcement practices regarding TIP still face various challenges. This study aims to analyze the challenges of TIP law enforcement in Indonesia and propose solutions from a criminal law perspective. The method used is normative-juridical legal research. The analysis shows that law enforcement efforts regarding TIP need to be strengthened through the application of maximum criminal sanctions, comprehensive protection for victims, increased capacity of officers, the use of digital technology in investigations, and strengthened international cooperation. With these steps, it is hoped that TIP law enforcement in Indonesia can be more effective in preventing, prosecuting, and breaking the chain of human trafficking crimes.